Галина Іванівна Мудрик: життя і досвід мудрої людини - Констанкевич, Ірина; Konstankevich, Iryna (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено огляду життя і науково-педагогічної діяльності Г. І. Муд- рик – кандидата філологічних наук, доцента, ветерана освіти з 50-літнім стажем роботи у провідному ВНЗ Волині, одного з фундаторів кафедри української літератури в середині 50-х рр. ХХ ст. This article provides an overview of the life and scientific-pedagogical activity of G. I. Mudryk − candidate of philological sciences, senior lecturer, a veteran of education with 50 years experience in the leading University Volyn, one of Fundator chair of Ukrainian literature from the 50s of the twentieth century.
Galina Mudryk: the Life and Experience of a Wise Man
Keywords: викладач; особистість; науково-педагогічний доробок; teacher; person; science and teaching experience